Management of developmental dysplasia of the hip in less than 24 months old children - Bulut, Mehmet; Gurger, Murat; Belhan, Oktay; Batur, Omer Cihan; Celik, Suat; Karakurt, Lokman (Springer Heidelberg, 2013)
Background: There is no consensus on the treatment of developmental dysplasia of the hip in children less than 24 months of age. The aim of this study was to present the results of open reduction and concomitant primary soft-tissue intervention in patients with developmental dysplasia of the hip in children less than 24 months of age. Materials and Methods: Sixty hips of 50 patients (4 male, 46 female) with mean age of 14.62 +/- 5.88 (range 5-24 months) months with a mean followup of 40.00 +/- 6.22 (range 24-58 months) months were included. Twenty five right and 35 left hips (10 bilaterally involved) were operated. Open reduction was performed using the medial approach in patients aged < 20 months (with Tonnis type II-III and IV hip dysplasias) and for those aged 20-24 months with Tonnis type II and III hip dysplasias (n = 47). However for 13 patients aged 20-24 months with Tonnis type IV hip dysplasias, anterior bikini incision was used. Results: Mean acetabular index was 41.03 +/- 3.78 degrees (range 34 degrees-50 degrees) in the preoperative period and 22.98 +/- 3.01 degrees (range 15 degrees-32 degrees) at the final visits. Mean center-edge angle at the final visits was 22.85 +/- 3.35 degrees (18 degrees-32 degrees). Based on Severin radiological classification, 29 (48.3%) were type I (very good), 25 (41.7%) were type II (good) and 6 (10%) were type III (fair) hips. According to the McKay clinical classification, postoperatively the hips were evaluated as excellent (n = 42; 70%), good (n = 14; 23.3%) and fair (n = 4; 6.7%). Reduction of all hip dislocations was achieved. Additional pelvic osteotomies were performed in 14 (23.3%) hips for continued acetabular dysplasia and recurrent subluxation. (Salter [n = 12]/Pemberton [n = 2] osteotomy was performed). Avascular necrosis (AVN) developed in 7 (11.7%) hips. Conclusion: In DDH only soft-tissue procedures are not enough, because of the high rate of the secondary surgery and AVN for all cases aged less than 24 months. Bone procedures may be necessary in the walking age group with high acetabular index.
Keywords: Anterior bikini incision; developmental dysplasia of the hip; medial approach